Designing Muslimheir Application As An Educational Game About Heritage (Case Study MAN 1 Bener Meriah) - Chandra Halim.M; Febri Mira Rizki (Al Makki Publisher, 2023)
Inheritance is property or property that is entitled to be received by heirs, legally must be divided fairly so as not to cause family division. This is used as a learning material taught to class XII MAN 1 Bener Meriah students. Based on the results of initial observations, learning at MAN 1 Bener Meriah usually still uses the monotonous lecture method. As a result, students' understanding tends to be minimal and students quickly forget it. So a heritage learning application is needed for class XII students to facilitate understanding of the material. One solution that can be used is the use of the Muslimheir application. Muslimheir app is an app that provides learning services about inheritance. This application is designed by utilizing the principles of educational games so that it can be used by all circles, especially among MAN 1 Bener Meriah students. The purpose of this study is to know the concept and testing of the Muslimheir application as a learning medium for inheritance. This research method uses an incremental model method, which consists of: analysis, design, coding and testing. The population of this study was all students of Class XII MAN 1 Bener Meriah. The sample included 20 students who were randomly drawn to try the Muslimheir app and then gave testimonials via Google Forms. The results showed that the Muslimheir application has a concept as an edu-game equipped with Faraidh, Game, History, Application Info, FAQ, and Calculate Inheritance features. Researchers concluded that based on testing 20 panelists, 90% of participants revealed that this application increased their understanding of the distribution of inheritance according to Islamic law. The results of validation tests by 4 expert validators show that the Muslimheir application has a score of 88,278 which means very good. Thus, the Muslimheir application can be used in learning related to inheritance in the future.